2011
DOI: 10.1371/journal.pone.0027219
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Toggling of Yeast Iso-1-Cytochrome c in the Oxidized and Reduced States

Abstract: To convert cyt c into a peroxidase-like metalloenzyme, the P71H mutant was designed to introduce a distal histidine. Unexpectedly, its peroxidase activity was found even lower than that of the native, and that the axial ligation of heme iron was changed to His71/His18 in the oxidized state, while to Met80/His18 in the reduced state, characterized by UV-visible, circular dichroism, and resonance Raman spectroscopy. To further probe the functional importance of Pro71 in oxidation state dependent conformational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The balance between the hydrophilic and hydrophobic moieties along the TRPs determines the LCST, and in this context, the LCST of a TRP is easily altered by the addition of chemical or biological stimuli. The influence of the cosolvents on the phase-transition behavior of the “smart” polymer has been explored experimentally, and it has been reported that extended polymeric globules collapse with increasing temperature. Although a number of studies about a variety of different additives are available in the literature, only a few studies are available to investigate the effect of biomolecules such as proteins on the responsive behavior of polymers. Very recently, our research group delineated the effect of biological stimuli on the phase behavior of polymer and found that different proteins affect the coil and globule transition in different ways.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The balance between the hydrophilic and hydrophobic moieties along the TRPs determines the LCST, and in this context, the LCST of a TRP is easily altered by the addition of chemical or biological stimuli. The influence of the cosolvents on the phase-transition behavior of the “smart” polymer has been explored experimentally, and it has been reported that extended polymeric globules collapse with increasing temperature. Although a number of studies about a variety of different additives are available in the literature, only a few studies are available to investigate the effect of biomolecules such as proteins on the responsive behavior of polymers. Very recently, our research group delineated the effect of biological stimuli on the phase behavior of polymer and found that different proteins affect the coil and globule transition in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Cyt c is an electron carrier which contains heme c that is coordinated with a protein scaffold by cysteine residues. Cyt c is in the shape of a prolate spheroid and the heme group is attached to it through two thioester bonds, that is, cysteine (Cys) 14 and cysteine (Cys) 17, and the “closed crevice” where the heme iron is held, with the axial ligands, histidine (His) 18 and the methionine (Met) 80 . Cyt c contains five α-helical segments which are N-terminal (residues 2–14), C-terminal (residues 87–103), and helical segments 49–55, 60–70, and 70–75. , Mb, which is a cytoplasmic heme protein, belongs to the globin superfamily of proteins containing 153 amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However Traditional HDX experiments use the relay-mechanism to explain the isotopic exchange in the gas-phase via charge-mediated exchanges in a timely-efficient manner [69][70][71][72] The HDX-TIMS experiments share some analogy with thermal energy HDX ion-molecule reactions used to probe conformational differences by Smith and coworkers, 73 reported that Trp59 and Met80 residues provide a unique hydrophobic environment to the heme crevice. 77,78 Without these interactions, the crevice opens up, exposing Thr78 and Pro71, which are residues involved in the formation and stabilization of the heme crevice due a network of hydrogen bonds around the heme group. 79 The interface formed by the interaction of the helices occurs immediately after the covalent binding of the heme group to the polypeptide via thioether bonds.…”
Section: Cia-hdx-tims-msmentioning
confidence: 99%